Somatic embryogenesis from mature split seeds of jaboticaba (Plinia peruviana (Poir) Govaerts) (Acta Scientiarum. Agronomy, 2020)
Plinia peruviana is a species that is native to Brazil and is important due to the taste and medicinal properties of its fruits. Young leaves and split mature seeds were used as explants to initiate somatic embryogenesis to obtain a large number of plants in a short period of time. Leaf discs were cultured in MS medium containing various concentrations of 2,4-D (2,4-dichlorophenoxyacetic acid) or picloram (4-amino-3,5,6-trichloro-2-pyridinecarboxylic acid). In the case of the mature seeds, various concentrations of glutamine, 2,4-D and a combination of auxin and BAP (6-benzylaminopurine) were tested for somatic embryogenesis induction. For somatic embryo maturation, several concentrations of PEG 6000 (polyethylene glycol; up to 90 g L-1) were tested. After 60 days of culture using leaf discs, callus formation occurred in all treatments, with the highest averages obtained with 10 Î¼M 2,4-D. However, these calluses did not form somatic embryos. For the cultured seeds, the best treatment was the MS medium with 1,000 mg L-1 glutamine and 10 Î¼M 2,4-D without BAP. The supplementation of 60 g L-1 PEG 6000 was sufficient to promote the maturation of the somatic embryos. Histological analyses of the calluses that were formed from leaf discs showed nonembryogenic characteristics. In contrast, the calluses that originated from mature seeds had small and round cells with little vacuolation, which are characteristics of embryogenic structures.